Ta’lim Al-Lughah Al ‘Arabiyyah fi ‘Asr Al-Thabiiy Al-Jadid fi Dhau’ Al-Ta’lim Al-Mudmaj - Puji Rahayu (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2021)
The learning process cannot be separated from the presence of the teacher. The role of the teacher in the learning process is the very dominant decisive factor in education in general, because the teacher plays a role in the learning process, where the learning process is the core of the educational process. During this pandemic, learning cannot take place face to face. In order to conduct distance learning online and offline, the choice of learning methods is very important because it will have an impact on the smooth implementation of learning. One method that can be used is the "blended learning" learning model. Blended learning is learning that combines face-to-face learning (traditional learning: lecture, assignment, question-and-answer, demonstration methods), and online learning through the use of different media and technology to support independent learning and provide learning experiences for students. Blended learning can be interpreted as a learning process that uses different approaches. The approach taken can use a variety of media and technology. Elements of blended learning-based learning combines face-to-face learning and e-learning that contains 6 (six) elements, namely: (1) face-to-face, (2) independent learning, (3) applications, (4) lessons, (5) cooperation, and (6) evaluation.لا يمكن فصل عملية التعلم عن وجود المعلم، فدور المعلم في عملية التعلم هو العامل الحاسم المهيمن للغاية في التعليم بشكل عام، لأن المعلم يلعب دورًا في عملية التعلم، حيث تكون عملية التعلم هي جوهر العملية التعليمية. خلال هذا الوباء، لا يمكن أن يتم التعلم وجهًا لوجه. من أجل إجراء التعلم عن بعد عبر الإنترنت وغير متصل، يعد اختيار طرق التعلم أمرًا مهمًا للغاية لأنه سيكون له تأثير على التنفيذ السلس للتعلم. إحدى الطرق التي يمكن استخدامها هي نموذج التعلم "التعلم المدمج". التعلم المدمج هو التعلم الذي يجمع بين التعلم وجهاً لوجه (التعلم التقليدي: المحاضرة والتعيين والأسئلة والأجوبة وطرق العرض التوضيحي)، والتعلم عبر الإنترنت من خلال استخدام وسائل الإعلام والتكنولوجيا المختلفة لدعم التعلم المستقل وتوفير الخبرات التعليمية للطلاب. يمكن تفسير التعلم المدمج على أنه عملية تعلم تستخدم مناهج مختلفة. يمكن أن يستخدم النهج المتبع مجموعة متنوعة من الوسائط والتكنولوجيا. تجمع عناصر التعلم القائم على التعلم المدمج بين التعلم وجهاً لوجه والتعلم الإلكتروني الذي يحتوي على ٦ (ستة) عناصر، وهي: (١) وجهاً لوجه (٢) التعلم المستقل، (٣) التطبيقات، (٤) دروس و (٥) تعاون و (٦) تقييم.